2023
DOI: 10.3389/fmars.2023.1146148
|View full text |Cite
|
Sign up to set email alerts
|

The impact of marine heatwaves on rocky intertidal communities: evidence of accumulative carryover effects of marine heatwaves

Abstract: The frequency and duration of marine heat waves (MHWs) have recently increased. There is therefore an urgent need to understand the response of marine organisms to MHWs. However, most estimates of MHW impacts on abundances include the effects of environmental stochasticity other than the MHWs. In addition, although MHWs sometimes persist for year-round or occur repeatedly for shorter periods, the accumulative carryover effects (ACEs)— the effects of sequential events accumulating additively over time— of MHWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Blanchette et al [30] have discovered patterns of diversity on a broad regional scale from southeast Alaska to southern California, with seven distinct biogeographical groups defined based on patterns in similarity. In the Southeast Pacific, Ibanez et al [11] and Valqui et al [10] have accomplished similar work by identifying localized patterns, shifts in biological compositions, and a shifting zone of transition following disturbance from El Niño in Peru between 4 • S and 14 • S. Each work concludes with a statement of need to carry forward census efforts on large-and small-region scales in unstudied or poorly studied areas in order to collect the necessary biogeographic data on contiguous and temporal scales [8,10,11,26,85]. Mussels (family Mytilidae) are a foundation species found throughout the intertidal zone and have increasingly become the subject of research due to their abundance worldwide, which positions them as a sentinel species for measuring the physiological responses and rates of mortality from environmental stress and human disturbance [1,[87][88][89][90][91].…”
Section: Research Conducted On Intertidal Ecosystems In the Pacificmentioning
confidence: 85%
See 2 more Smart Citations
“…Blanchette et al [30] have discovered patterns of diversity on a broad regional scale from southeast Alaska to southern California, with seven distinct biogeographical groups defined based on patterns in similarity. In the Southeast Pacific, Ibanez et al [11] and Valqui et al [10] have accomplished similar work by identifying localized patterns, shifts in biological compositions, and a shifting zone of transition following disturbance from El Niño in Peru between 4 • S and 14 • S. Each work concludes with a statement of need to carry forward census efforts on large-and small-region scales in unstudied or poorly studied areas in order to collect the necessary biogeographic data on contiguous and temporal scales [8,10,11,26,85]. Mussels (family Mytilidae) are a foundation species found throughout the intertidal zone and have increasingly become the subject of research due to their abundance worldwide, which positions them as a sentinel species for measuring the physiological responses and rates of mortality from environmental stress and human disturbance [1,[87][88][89][90][91].…”
Section: Research Conducted On Intertidal Ecosystems In the Pacificmentioning
confidence: 85%
“…Today, much of the intertidal research in the eastern and western Pacific has occurred along semi-continuous coastlines or a patchwork of latitudes with a focus on characterizing localscale species diversity and abundance, spatial turnover, hierarchical structure, range shifts, and the relationship between biological and oceanographic processes [1,8,11,13,19,83,84]. In the western Pacific, Okuda et al [13] have discerned regional-scale gradients in richness and beta (turnover) diversity, and more recently, small-scale accumulative carryover effects have been identified among functional and trophic groups during and after chronic marine heatwaves in Hokkaido [85]. In the central north Pacific, Konar et al [86] have identified depth-stratified differences in taxonomic hierarchies, invertebrate abundance and macro-algal biomass in intertidal and subtidal communities in Kodiak, Kachemak Bay, and Prince William Sound.…”
Section: Research Conducted On Intertidal Ecosystems In the Pacificmentioning
confidence: 99%
See 1 more Smart Citation
“…While various year-to-year environmental fluctuations may drive community dynamics in rocky intertidal assemblages (Thompson et al ., 2002; Menge et al ., 2003; Ishida et al ., 2023), their influences on the results of this study should be small. From October 2020 to October 2021, there was no other disturbance that would cause massive mortality (e.g., earthquake, tsunami, typhoon, ice scouring, marine heatwave, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of HAB on each species ( i ) at the regional scale ( ES REGION,i ) and each functional group ( j ) at each shore ( k ) ( ES SHORE,j,k ), we calculated the effect sizes ( ES ) of the abundance ( A ) from the pre-HAB period (2004–2020) to the post-HAB period (2021) with the following formulas (Iwasaki et al ., 2016; Noda et al ., 2017; Iwasaki & Noda, 2017; Ishida et al ., 2023): where log ( A REGION,i,post − HAB ) represents the log 10 (abundance) of each species in the post-HAB year, log ( Ā REGION,i,pre−HAB ) and SD ( log ( A REGION,i,pre−HAB )) represent the mean and standard deviation of the log 10 (abundance) of each species during the pre-HAB period, respectively; log ( A REGION,j,k,post − HAB + 0.5) represents the log 10 (abundance + 0.5) of each functional group at each shore in the post-HAB year, log ( Ā REGION,j,k,pre − HAB + 0.5) and SD log ( A REGION,j,k,pre − HAB + 0.5) represent the mean and standard deviation of log 10 (abundance + 0.5) of each functional group at each shore during the pre-HAB period, respectively. An effect size greater than 1.96 in absolute value suggests that the abundance in the post-HAB year changed significantly compared with the pre-HAB period.…”
Section: Methodsmentioning
confidence: 99%